Utilization of Vicryl Bridging Mesh in Orthotopic Liver Transplantation to Achieve Tension-Free Abdominal Wall Closure: A Case Series - Ea-sle Chang; Alice Martino; Adam Welu; Mustafa Nazzal (Case Reports in Surgery)
Difficulty in primary fascial closure of the abdomen in transplant patients is a common challenge. Abdominal wall tension may have detrimental effects on the newly transplanted graft due to compression, and blood flow hindrance, potentially leading to ischemia or thrombosis and possibly graft failure. Furthermore, patients will be at risk of developing fascial ischemia and dehiscence. Myocutaneous flaps, temporary closure with silastic mesh, abdominal wall transplants, and even graft reduction, bowel resection, and splenectomies have been practiced with varying degrees of success. In this study, we present four cases of patients who underwent orthotopic liver transplantation (OLT) with bridging Vicryl knitted mesh (ETHICON VKML VICRYL-Polyglactin 910-30×30 cm) to relieve the tension during the closure. Our results show that these patients, despite having a high average Model End-Stage Liver Disease (MELD) score of 25, had a good liver function at the time of discharge and continue to upon follow-up. They had a relatively short length of stay (LOS) in both the intensive care unit (ICU) and in the hospital, an average of 3.5 days and 9 days, respectively. Our case series successfully show that utilizing a bridging Vicryl knitted mesh is a reasonable approach to attain tension-free abdominal closure in OLT with satisfying results.